2020
DOI: 10.33448/rsd-v9i10.8282
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de agrotóxicos no cultivo de grãos e sua relação com a saúde e ambiente

Abstract: Este estudo teve por objetivo identificar como ocorre o manejo de agrotóxicos utilizados no cultivo de grãos e sua relação com a saúde e o ambiente em um município da região da Serra Catarinense. Foram entrevistados 79 agricultores que cultivam grãos (soja, milho e feijão) para coleta de informações sociodemográficas e de suas propriedades, sobre o uso, transporte, armazenamento e descarte das embalagens vazias. Quase metade dos agricultores transporta agrotóxicos em carro fechado, junto com outros produtos e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Research in Brazil has shown cases of farmer intoxication by pesticides related to the occurrence of chronic diseases 27 , 28 , 29 . As shown by some studies in the mountainous region of Santa Catarina, where agriculture is one of the main economic drivers, there are deficiencies in the use and handling of these chemicals, as well as cases of acute intoxication and even associations with diseases 10 , 11 . An international study indicated an association between CKD and chronic exposure to specific pesticides 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Brazil has shown cases of farmer intoxication by pesticides related to the occurrence of chronic diseases 27 , 28 , 29 . As shown by some studies in the mountainous region of Santa Catarina, where agriculture is one of the main economic drivers, there are deficiencies in the use and handling of these chemicals, as well as cases of acute intoxication and even associations with diseases 10 , 11 . An international study indicated an association between CKD and chronic exposure to specific pesticides 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Santa Catarina’s agriculture is developed with high technological levels, applied in intensive production systems and with high added value 9 ; despite this, agricultural production in the region is based on conventional cultivation with the use of pesticides for the management of agricultural crops. The expressive and frequent use of pesticides causes damages with environmental and human contamination 10 , 11 . In relation to human health, the harmful effects of the use of pesticides are diverse and can cause acute or chronic poisoning 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se que nos municípios citados anteriormente, entre as culturas agrícolas observa-se principalmente o cultivo de feijão, fumo, soja, arroz, mandioca, morango, cebola, erva mate, tomate e milho, tendo este último uma posição relevante, visto que é produzido em todos os municípios. A intensidade do uso de agrotóxicos nessas culturas, sobretudo em grãos, deve ser considerada, pois demanda grandes quantidades, podendo chegar a 40 tipos de agrotóxicos em um único município 24 .…”
Section: Discussionunclassified
“…A faixa etária dos agricultores variou de 18 a 58 anos, dos quais: dois possuíam idades entre 18 a 25 anos, dois entre 26 a 35 anos, três entre 36 a 45 anos, cinco entre 46 a 55 anos e um com 58 anos. Perfil semelhante ao encontrado na literatura, em que a maioria dos agricultores é homem com idade entre 41 e 60 anos (Pedroso et al, 2020).…”
Section: Caracterização Dos Agricultores Familiaresunclassified